METODE DAKWAH STRUKTURAL KIAI AHMAD FAUZAN - Huda, Muhammad Misbahul (Jurnal Dakwah, 2020)
Changes in space and time also have an impact on changing patterns, approaches, methodologies, and characteristics of dakwah. Therefore da'wah can be situational and contextual according to the space and time that surrounds it. The understanding of a da'i in understanding Islamic da'wah comprehensively will give rise to a perspective in which the approach, dimensions and dynamics that must be prepared and what kind of model will be used in da'wah activities will determine the success of the da'wah activity. Kiai Ahmad Fauzan is one of the scholars who can be said to be visionary. Due to in-depth reading in terms of conditions, situations, and abilities, finally Kiai Ahmad Fauzan, besides using a cultural approach, also uses a structural approach. The structural approach was used as a method of da'wah which was fairly effective for him. Because, from the use of the structural da'wah method, Kiai Ahmad Fauzan can make it easier to coordinate, regulate, and ratify the rules that should apply or not. The methods of proselytizing Kiai Ahmad Fauzan found in this study are methods of political da'wah and methods of proselytizing education. This research uses descriptive-qualitative research with historical analysis in the form of "oral or spoken" from historians and people who have a close relationship with the subject or object under study.